2021
DOI: 10.1111/ajsp.12497
|View full text |Cite
|
Sign up to set email alerts
|

Who moved with you? The companionship of significant others reduces movers’ motivation to make new friends

Abstract: This research investigated how residential moves with versus without the companionship of significant others would affect people’s motivation to make new friends. Studies 1a and 1b showed that the companionship of significant others predicted fewer new friends among university students who moved within the same country (Study 1a) and to a different country (Study 1b), suggesting that the companionship of significant others was associated with a lower level of motivation to make new friends. In Study 2, the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…Couples with higher levels of companionship showed higher positive affect in Study 1, whereas the effects in Studies 2 and 3 were smaller and nonsignificant yet in the same direction. This finding is consistent with a study showing that the companionship of a significant other was related to stronger positive affect, which reduced motivation to make new friends after moving to a new location; negative affect was unrelated (Li et al, 2022). Similarly, another study found that higher positive affect was associated with companionship, but negative affect had a more attenuated effect (Davidson et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…Couples with higher levels of companionship showed higher positive affect in Study 1, whereas the effects in Studies 2 and 3 were smaller and nonsignificant yet in the same direction. This finding is consistent with a study showing that the companionship of a significant other was related to stronger positive affect, which reduced motivation to make new friends after moving to a new location; negative affect was unrelated (Li et al, 2022). Similarly, another study found that higher positive affect was associated with companionship, but negative affect had a more attenuated effect (Davidson et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…Those in the mobility mindset condition spontaneously mentioned more loneliness and sadness than those in the stability and control conditions; the more loneliness and sadness they anticipated, the more motivated they were to make new friends. A recent study, however, found that when people are moving to a new location with their family members, friends, or romantic partner, they are not as motivated to expand their social networks as when they are moving to a new location without any close others (Li et al, 2021).…”
Section: Psychological Implications Of Residential Mobilitymentioning
confidence: 99%
“…In addition, recent research points to the critical role partners play in network development for immigrants. Li et al (2022) found that immigrants who moved with a companion were less likely to make new friends in the host environment. They argued that immigrants are less motivated to actively establish new connections when they can derive the necessary emotional support from their significant other.…”
Section: Discussionmentioning
confidence: 97%